The Recess - Lee, Sophia, 1750-1824 (Book collections on Project MUSE., 2000)
First published in an era when most novels about young women concentrated on courtship and ended with marriage, The Recess daringly portrays women involved in political intrigues, overseas journeys, and even warfare. The novel is set during the reign of Elizabeth I and features as narrators twin daughters of Mary, Queen of Scots, by a secret marriage. One of the earliest Gothic novels, The Recess pioneered the genre of historical fiction. The novel was also one of the first to describe characters and events from conflicting points of view and was wildly popular in its day.